The Relationship between Personal Factors and Institutional Environment on English Learning Motivation in Islamic Boarding Schools: A Study of the L2 Motivational Self System - Luzain Habibah Al-Athar; Irsyad Nugraha; Mohammad Soni (Jurnal Ragam Pengabdian, 2026)
This study examines the motivational orientation of Islamic boarding school students toward English language learning and challenges the common assumption that religious identity may reduce acceptance of English as a global language. The research aims to describe students’ perceptions of the importance of English, sources of motivation, perceived learning difficulty, and preferred learning materials within the pesantren context. This study employed a quantitative descriptive survey design. Data were collected through a structured online questionnaire distributed to students who actively participated in English classes. Total sampling was applied to respondents who completed the questionnaire. The instrument consisted of closed-ended questions measuring perceived importance of English, motivational sources, level of difficulty, and instructional preferences. The collected data were analyzed using descriptive statistical techniques in the form of frequency and percentage distribution. The findings indicate that most students consider English an important subject despite perceiving it as difficult. Internal motivation emerged as the dominant source of learning drive, followed by teacher encouragement. Students showed greater interest in communicative daily conversation materials than in religious text-based materials. These results suggest that students’ motivation is future-oriented and internally driven rather than externally imposed. In conclusion, English learning motivation among Islamic boarding school students is characterized by positive perception, strong self-driven orientation, and resilience despite perceived difficulty. The findings confirm that religious educational settings do not inherently hinder students’ engagement with English as a global language.